Exploring the Health Literacy Behavior Patterns of Male Patients Using an Interpretable Method - Huang L; Jin Y; Chien CW; Xu Q; Chuang YC; Tung TH (Dove Medical Press, 2024)
Lizhen Huang,1,* Yanjun Jin,2,* Ching-Wen Chien,3 Qinyi Xu,3 Yen-Ching Chuang,4- 6 Tao-Hsin Tung6,7 1School of Economics and Management, Fuzhou University, Fuzhou, Fujian, 350108, People's Republic of China; 2Department of Urology, Taizhou Hospital of Zhejiang Province Affiliated to Wenzhou Medical University, Linhai, Zhejiang, 317000 People's Republic of China; 3Institute for Hospital Management, Tsing Hua University, Shenzhen Campus, Shenzhen, People's Republic of China; 4Business College, Taizhou University, Taizhou, Zhejiang, 318000, People's Republic of China; 5Institute of Public Health & Emergency Management, Taizhou University, Taizhou, Zhejiang, 318000, People's Republic of China; 6Key Laboratory of Evidence-Based Radiology of Taizhou, Linhai, Zhejiang, 317000, People's Republic of China; 7Evidence-based Medicine Center, Taizhou Hospital of Zhejiang Province Affiliated to Wenzhou Medical University, Linhai, Zhejiang, 317000, People's Republic of China*These authors contributed equally to this workCorrespondence: Yen-Ching Chuang; Tao-Hsin Tung, Email yenching.chuang@gmail.com; ch2876@gmail.comBackground: Improving overall and individual health literacy is a major focus of national initiatives in China and similar initiatives globally. However, few studies have examined the identification and improvement of individual health literacy levels, especially among patients.Purpose: To develop an interpretable method with decision rules to assess the health literacy levels of male patients and identify key factors influencing health literacy levels.Methods: Using a convenience sampling method, we conducted on-site surveys with 212 male patients of a hospital in China from July 2020 to September 2020. The questionnaire was developed by the Ministry of Health of the People's Republic of China. A total of 206 of the completed surveys were ultimately included for analyses in this study. The rough set theory was used to identify conditional attributes (ie, key factors) and decision attributes (ie, levels of health literacy) and to establish decision rules between them. These rules specifically describe how different combinations of conditional attributes can affect health literacy levels among men.Results: Basic knowledge, concepts, and health skills are important in identifying whether male patients have health literacy. Health skills, scientific health concepts, healthy lifestyles and behaviors, infectious disease prevention and control literacy, basic medical literacy, and health information literacy can be identified as cognitive behaviors with varying degrees of health literacy among patients.Conclusion: This model can effectively identify the key factors and decision rules for male patients' health literacy. Simultaneously, it can be applied to clinical nursing practice, making it easier for hospitals to guide male patients to improve their health literacy.Keywords: health literacy, male patients, key factors, decision rules, rough set theory, RST